2020
DOI: 10.1111/hepr.13586
|View full text |Cite
|
Sign up to set email alerts
|

Changes in disease characteristics of primary biliary cholangitis: An observational retrospective study from 1982 to 2016

Abstract: Aim Disease characteristics of primary biliary cholangitis have changed recently. However, detailed studies on the subject have been limited. Therefore, we aimed to clarify disease characteristics of patients with recent primary biliary cholangitis using the cohort from Niigata University and 21 affiliated hospitals. Methods Overall, 508 patients were enrolled in this study from 1982 to 2016, divided into three cohorts according to their year of diagnosis: ≤1999, 2000–2009 and ≥2010. We compared differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Although this disease mostly affects middle-aged females, the percentage of males is gradually increasing. 1 A Japanese study reported that from 1980 to 1998, 69.9% of patients with PBC were asymptomatic during diagnosis, and the percentage of initially symptomatic patients who had a total Figure 1 Strategy of this study. A total of 483 with primary biliary cholangitis were enrolled.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…Although this disease mostly affects middle-aged females, the percentage of males is gradually increasing. 1 A Japanese study reported that from 1980 to 1998, 69.9% of patients with PBC were asymptomatic during diagnosis, and the percentage of initially symptomatic patients who had a total Figure 1 Strategy of this study. A total of 483 with primary biliary cholangitis were enrolled.…”
Section: Introductionmentioning
confidence: 85%
“…This retrospective multicenter analysis included all incident and prevalent alive cases of definite or probable PBC recorded between 1 January 1982, and 31 December 2014 in Niigata University Hospital and a related hospital. The original data in this study were the same as that previously reported by us 1 . The diagnosis of PBC was made based on the criteria established by the Intractable Hepato‐Biliary Diseases Study Group of Japan 12 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations